Econometric models of the world commodity market (Japan : Institute of Developing Economies, 1984)
The main purpose of this study was to specify and estimate an econometric model of the world fiber market, with emphasis on the cotton production and consumption for the major world fiber market participants. In addition to forecasting, the model is used to estimate the impact of some important market and policy developments. Analysis of these developments provides timely and relevant information for many groups and individuals with interest in the fiber market.
Economic Research Unit Center for Analysis of Developing Economies, University of Pennsylvania.
ELSA technical Report 1.
aia 07/06/2018
Loans
Keywords: Econometric models; Econometrics